Development of JINEMAM Learning Model - Dwi Candra Setiawan; Deny Setiawan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
The research aims to produce a learning model that is expected to be easy, effective and practically applied in the learning process. The model developed is the JINEMAM model which is a combination of the Jigsaw, Example Non Example and Make a Match model. This research in its development process uses the 4D development model from thiagarajan namely Define, Design, Develop and Disseminate. The instruments used were validation sheets, legibility questionnaires and pretest-posttest questions. For product trials and legibility using 32 students of the 2014 Biology study program. The results of the data analysis showed that the learning model was very valid. Based on the results of the analysis it can be concluded that the learning model is feasible to be used in the learning process.